Association between adverse childhood experiences and brain volumes among Japanese community-dwelling older people: Findings from the NEIGE study. (February 2022) - Koyama, Yuna; Fujiwara, Takeo; Murayama, Hiroshi; Machida, Masaki; Inoue, Shigeru; Shobugawa, Yugo
Abstract: Background: Adverse childhood experiences (ACEs) can affect later-life health outcomes via brain structural differences. However, there is no sufficient empirical evidence about whether brain morphological differences remain until old ages. Objective: We examined the association between ACEs and brain volumes among older individuals. Participants and setting: Residents aged 65–84 years in Tokamachi City, Japan, were randomly recruited, and 491 participants were included in the analysis. Methods: ACEs were assessed with a self-reported questionnaire. The volumes of seven brain regions of interests were evaluated via structural magnetic resonance imaging. Results: In total, 143 (27.1%) participants experienced one ACE and 33 (6.7%) two or more ACEs. Participants with two or more ACEs had a larger anterior cingulate cortex volume (B = 0.346, 95% confidence interval [CI] = 0.04 to 0.66) and smaller hippocampal (B = −0.287, 95% CI = −0.58 to 0.001) and amygdala (B = −0.313, 95% CI = −0.59 to −0.03) volumes. Interestingly, we observed a distinct association between deprivation and threat. That is, deprivation was associated with a smaller amygdala volume (B = −0.164, 95% CI = −0.32 to −0.01) and threat with a larger anterior cingulate cortex volume (B = 0.401, 95% CI = 0.11 to 0.70). Conclusions: ACEs were associated with the volumes of brain regions such as anterior cingulate cortex, hippocampus, and amygdala, which are responsible for emotion and self-regulation in older population. The effect of ACEs on the amygdala was commonly driven by deprivation experiences and that on the anterior cingulate cortex by threat. Highlights: Brain morphological differences in old age due to adverse childhood experiences have not been well explored. Older people with more adverse experiences had smaller hippocampus. Those with more adversities, mainly threat, showed larger anterior cingulate cortex. More adversities associated with smaller amygdala, mainly driven by deprivation.